2011
DOI: 10.1088/0004-637x/740/2/61
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Phase Variations of the 55 Cancri System

Abstract: Characterization of the composition, surface properties, and atmospheric conditions of exoplanets is a rapidly progressing field as the data to study such aspects become more accessible. Bright targets, such as the multi-planet 55 Cancri system, allow an opportunity to achieve high signal-to-noise for the detection of photometric phase variations to constrain the planetary albedos. The recent discovery that innermost planet, 55 Cancri e, transits the host star introduces new prospects for studying this system.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Kane et al (2011) showed that, at visible wavelengths, the modulation due to planet "b" may not be negligible compared with that of planet e, depending of course on the respective albedos of planets e and "b". Characterizing the properties of planet e by orbital photometry thus requires the ability to distinguish between the two components, which is an additional challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Kane et al (2011) showed that, at visible wavelengths, the modulation due to planet "b" may not be negligible compared with that of planet e, depending of course on the respective albedos of planets e and "b". Characterizing the properties of planet e by orbital photometry thus requires the ability to distinguish between the two components, which is an additional challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Winn et al (2011) and Demory et al (2011) both independently report the photometric detection of a transit of 55 Cnc e. In addition, Kane et al (2011) calculate combinations of expected planetary brightness variations with phase, for which knowledge of planetary radius is useful.…”
Section: The Transiting Super-earth 55 Cnc Ementioning
confidence: 99%
“…The detection of the exoplanet emission spectra was also possible through high-resolution spectroscopy (Brogi et al 2012;Rodler et al 2012;de Kok et al 2014). The measurement of phase variations relies on the detection of the flux variation along the planet's orbit as it alternately presents its day and night hemisphere to us (e.g., Knutson et al 2009;Kane et al 2011). These techniques represent the current front line of exoplanet characterization and are limited only by flux measurement precision that they impose as a result of the low planet-star flux ratio (e.g., in the most favorable cases, for a Jupiter sized planet with a 3 day period orbit F Planet /F Star ≈ 10 −4 in the visible and F Planet /F Star ≈ 10 −3 in the IR).…”
Section: Introductionmentioning
confidence: 99%